Renewable energy : power for a sustainable future (United Kingdom : Oxford university press, 2012)
Introducing renewable energy / Godfrey Boyle, Bob Everett and Gary Alexander -- Solar thermal energy / Bob Everett -- Solar photovoltaics / Godfrey Boyle -- Bioenergy / Dick Morris and Jonathan Scurlock -- Hydroelectricity / Janet Ramage -- Tidal power David Elliott -- Wind energy / Derek Taylor -- Wave energy / Les Druckers -- Geothermal energy / John Garnish and Geoff Brown -- Integrating renewable energy / Bob Everett and Godfrey Boyle -- Appendix A. Energy arithmetic : a quick reference -- Appendix B. Levelized costs of renewable energy
Includes bibliographical references and index.
Keywords: Renewable energy sources